El autorretrato y la identidad en la actualidad. - Rogel Albán, Ronald Segundo (2016)
Addressing the study of "THE AUTHORRETRATE AS AN ARTISTIC ELEMENT QUESTIONER OF IDENTITY" implies to develop a thorough investigation on the influence and relevance of how the person is affected and their own identity, also be able to approach to identify something as intrinsic as their personality, Their gestures and attitudes that are what characterize us as human beings and identify us. To make a portrait is to submit to the model the different forms of analysis, be these technical, artistic, psychological, to be able to understand and decipher their forms and the whole anthropometric context of their face, this implies the management of the canon, tonalities, ethnics and modifications As the body art, with this diversity of characteristics can be handled a portrait appreciating every detail with which human beings are different in their likeness. On the other hand, the self-portrait implies a self-evaluation and a formal, technical and psychological introspection of the personality of the author, this mimesis about the gestures and the own character, is a graphic-visual reflection of its creator. The fundamentals are these theoretical, technical, historical, artistic, philosophical and aesthetic; Have served as a reference for the realization of this research work and in the personal has meant an excellent academic experience with which revolutionary concepts about the meaning of self-portrait in the work of art have been reached, broadening criteria in an aesthetic discourse. In approaching this self-portrait looking for details from a different perspective, it resulted in several sketches to continue formulating a mature idea about the final project, the materials contributed the effects with which they were intended to visualize these respective images that speak of the self-portrait that they describe without Is involved the face in these works, made with pencils with graphite HB, 6B integrating the technique of the pen and strengthening the color with the watercolor, to make mixed these works was intended to enrich with the diversity of materials the details with which they are composed This proposal denominated Mimesis of the self-portrait. When we speak of self-portrait we automatically understand that it refers exclusively to the bust area and focuses specifically on that area, this global compendium has been to understand the self-portrait as a mirror image of the author's face, but that face with its head contains a body that Are united and inseparable, that is why this research strengthens that union by exposing that the self-portrait can be any wall of the body that conforms that face, this vision modifies the perspective that can be thought towards a reflection that perhaps had not been proposed in a self-portrait and Opens a field of possibilities to be able to realize self-portraits with details of any area of ​​the body, thus determining that everything is a self-portrait because it is part of the author. As a conclusion we leave an open door on the possibility of being able to construct self-portraits without involving the face as the only compendium, expanding horizons and anthropomorphic perspectives globalizing them so that we can see similar proposals in future in which we appreciate details that announce the self-portrait without being involved Face on it. Traductor de Google para empresas:Google Translator ToolkitTraductor de sitios webGlobal Market Finder